Formability and deformation mechanism of Ti-6Al-4V sheet under electropulsing assisted incremental forming. (1st October 2020) - Ao, Dongwei; Gao, Jun; Chu, Xingrong; Lin, Shuxia; Lin, Jun
Graphical abstract: Highlights: Formability increased greatly under electropulsing assisted incremental forming. Electropulsing decreases strong texture strength, delaying the crack propagation. Anisotropic microstructure tends to be uniform during EAIF. Abstract: Electropulsing assisted incremental forming as an advanced technology could enhance the formability of hard-to-deform metal. However, the mechanism behind this improvement has not been clearly investigated. In this work, the texture development, fracture characteristic, strain variation and microstructure evolution were analyzed to study the deformation behaviors of Ti-6Al-4V alloy during electropulsing assisted incremental forming. The effect of orthotropic basal texture evolution on the crack propagation behavior presented that the electropulsing decreased the strong texture strength along the transverse direction, delaying the crack propagation along the rolling direction. Moreover, electropulsing caused the (0 0 0 1) base texture weakening, and the weakening of anisotropy behaviors led to the formability enhancement. The maximum deformation height of 21.7 mm and the forming angle of 66.5° were obtained. The deformation height was increased by 417.9% compared to conventional ambient incremental forming. The strain analysis results showed that the thickness strain difference along the rolling and transverse directions was reduced under the electropulsing. It was consistent with the phenomenon that the crack propagation direction along the rolling direction at room temperature was changed to the rolling and transverse directions under electropulsing. Another important observation on research was that anisotropic microstructure along different directions tended to be uniform due to the occurrence of dynamic recrystallization under electropulsing.